COMPARATIVE ANALYSIS OF POST-TENSIONED FLAT SLAB WITH CONVENTIONAL DESIGN USING BUILDING INFORMATION MODELLING (BIM) INTEGRATION IN TOWER STRUCTURE - Sjah, Jessica; Alfredo,; Rarasati, Ayomi Dita; Trigunarsyah, Bambang (Journal of Applied Engineering Science, 2025)
The tower structure consisted of 13 floors and a roof, with a maximum elevation of 52.4 meters, and was studied in this research. Classified under Seismic Design Category D with a risk factor of IV, it underwent the design process using both conventional methods (CONV) with a dual system (open-frame and special shear wall) system and compared to the post-tensioned flat slab (PTFS) method, integrated with Building Information Modelling (BIM) through ETABS 21 and Revit 2023 software. In the PTFS structural system, seismic forces were resisted by perimeter frames and shear walls. While gravity columns in the PTFS structure did not directly withstand seismic forces, they were designed using the compatibility displacement method. The PTFS structure had a lighter structural mass but greater stiffness than CONV structural system, resulting in decreased story drift and displacement but higher values of story shear and overturning moment. Through analysis and volume cost calculations, the study demonstrated cost savings of $221,118, equivalent to 10.2% of the structural cost, by implementing the post-tensioned flat slab system.
Keywords: building information modelling (BIM), post tensioned flat slab, deformation compatibility, concrete construction, seismic design